Cu/Electrochemically reduced graphene oxide layered nanocomposite for non-enzymatic H2O2 sensor. (2021) - Temur, Elif; Eryiğit, Mesut; Kurt Urhan, Bingül; Demir, Ümit; Öznülüer Özer, Tuba
Abstract: In this present study, we modified the Au surface with nanocomposite containing Cu nanoparticles and electrochemically reduced graphene oxide (ERGO) to increase the electrocatalytic performance of Au electrode for nonenzymatic amperometric detection of H2 O2 . The morphology and structural properties of the Cu/ERGO nanocomposites were investigated by XPS, XRD, STM and SEM techniques. The Cu/ERGO nanocomposite electrode displayed good performance for the electrochemical detection of H2 O2, compared to naked Au and Cu-modified Au electrodes, in terms of low working potential (at around −0.2 V), high sensitivity (20 μA cm −2  mM −1 ), and low detection limit (1.87 × 10 −9  mol.L −1 ).